2019
DOI: 10.1037/sgd0000344
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bisexual discrimination as insidious trauma and impacts on mental and physical health.

Abstract: Using a minority stress framework (Meyer, 2003), and conceptualizing antibisexual discrimination as a type of trauma, we examined relations between experiences of antibisexual discrimination, trauma symptoms, internalized biphobia, depression symptoms, and physical health in a sample of 387 selfidentified bisexual adults from the United States who completed an online survey. Path analysis using structural equation modeling indicated partial support for the hypothesized model. Antibisexual experiences from hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…Previous research has documented links between stigma-related stress, trauma symptoms, and physical and mental health (Arnett et al, 2019). As a potentially health-compromising response to chronic and pervasive multilevel systemic oppression, hypervigilant experiences as narrated by our participants elicited emotional and behavioral reactions (e.g., negative emotions such as fear and anxiety, self-monitoring) and interpersonal reactions (mistrust, social avoidance, and isolation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has documented links between stigma-related stress, trauma symptoms, and physical and mental health (Arnett et al, 2019). As a potentially health-compromising response to chronic and pervasive multilevel systemic oppression, hypervigilant experiences as narrated by our participants elicited emotional and behavioral reactions (e.g., negative emotions such as fear and anxiety, self-monitoring) and interpersonal reactions (mistrust, social avoidance, and isolation).…”
Section: Discussionmentioning
confidence: 99%
“…Vigilance may be an adaptive coping response used by LGBTQ individuals to avoid discrimination and prejudice (Meyer, 2003); however, acute experiences of discrimination (e.g., threat of physical violence) or chronic anticipation of prejudice or rejection (e.g., being fired from one's job) may lead to hypervigilance consistent with reactions to trauma (Keating & Muller, 2020). For example, a recent study based on a sample of bisexual-identified individuals found that experiences of antibisexual discrimination and prejudice were associated with trauma symptoms and subsequent poorer physical and mental health (Arnett et al, 2019).…”
Section: Stigma-related (Minority) Stress and Hypervigilancementioning
confidence: 99%
“…Another explanation, as indicated previously, is that bisexual people face additional prejudice and discrimination in addition to those directed toward LG persons. The literature contains consistent negative portrayals of bisexuals, mostly from heterosexuals but also from within the LG community (Arnett et al., 2019). By being poorly understood, bisexuals are often stereotyped as confused, lacking courage and indecisive (Kleese, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…According to Arnett et al. (2019), bisexuals are subjected to additional prejudice and discrimination that leads to unique stressors, in addition to those directed toward gay and lesbian persons. Similarly, Green et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested an association between being the target of heterosexist forms of harassment and symptoms of traumatic stress (Arnett et al., 2019; Dworkin et al., 2018). Synergistic experiences of bias and discrimination from racially and sexually marginalized social positions can amplify one's risk of psychological health disparities (Bowleg, 2008; Cole 2009).…”
mentioning
confidence: 99%